PUTUSAN HAKIM ATAS PEMENUHAN HAK-HAK ISTRI PADA KASUS CERAI GUGAT DALAM PERSPEKTIF CEDAW - Islamy, Athoillah; Abduh, Muhammad (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2023)
This study aims to identify the dimension of gender justice in the judge's decision on the divorce case in the Tasikmalaya City Religious Court Decision No. 2000/Pdt. G/2021/PA Tmk which requires the husband (defendant) to pay 'iddah, mut'ah, and madhliyah to the wife (plaintiff). This normative-empirical legal research uses a philosophical approach. The principle of gender equality in CEDAW becomes the theory of analysis of the subject matter of this study. The results of the study show that there is a dimension of gender justice in the judge's decision at the Tasikmalaya City Religious Court No. 2000/Pdt.G/2021/Pa.Tm which is in line with the three principles of the CEDAW convention.  First, the principle of substantive equality in the judge's gender-fair decision for the rights of plaintiffs is manifested juridically in the decision of the Tasikmalaya City Religious Court. Second, the principle of non-discrimination in the judge's decision that is gender fair to the plaintiff's rights based on the defendant has no longer provided a living. Third, the principle of state obligation on gender-fair judges' decisions for plaintiffs' rights based on gender-responsive laws on women's rights after divorce. The theoretical implications of this study show that the principle of gender mainstreaming in the CEDAW convention can be transformed into the decision of a Religious Court judge regarding a lawsuit case. The limitation of this study has not examined the variety of factors that often make judges passive, so that if the plaintiff does not demand a grant from the defendant, then the plaintiff does not get material rights from the plaintiff.